INFLUENCE OF PROVINCIAL FINANCIAL PERFORMANCE ON POVERTY WITH ECONOMIC GROWTH AS INTERVENING - Fery Panjaitan (Universitas Cenderawasih, 2021)
This study aims to determine the effect of regional financial performance on poverty with economic growth as an intervening variable. The population in this study is 33 provinces in Indonesia for the period 2011-2019. This study uses the PLS-SEM (Partial Least Square-Structural Equation Modeling) model with the WARPPLS 7.0 application by measuring the outer model test, inner model test, model fit test, and variance accounted for (VAF). The results of the research that the ratio of regional independence and PAD effectiveness ratios have no effect on poverty, regional financial efficiency ratios and activity ratios have a significant positive effect and the PAD growth ratio has a significant positive effect. Economic growth has a significant positive effect on poverty. While the results of the indirect effect of economic growth variables do not mediate the effect of financial performance as measured by the ratio of regional independence, PAD effectiveness ratio, regional financial efficiency ratio, activity ratio, and PAD growth ratio to poverty